Aging, Clonality, and Rejuvenation of Hematopoietic Stem Cells. Issue 8 (August 2016) - Akunuru, Shailaja; Geiger, Hartmut
Abstract : Aging is associated with reduced organ function and increased disease incidence. Hematopoietic stem cell (HSC) aging driven by both cell intrinsic and extrinsic factors is linked to impaired HSC self-renewal and regeneration, aging-associated immune remodeling, and increased leukemia incidence. Compromised DNA damage responses and the increased production of reactive oxygen species (ROS) have been previously causatively attributed to HSC aging. However, recent paradigm-shifting concepts, such as global epigenetic and cytoskeletal polarity shifts, cellular senescence, as well as the clonal selection of HSCs upon aging, provide new insights into HSC aging mechanisms. Rejuvenating agents that can reprogram the epigenetic status of aged HSCs or senolytic drugs that selectively deplete senescent cells provide promising translational avenues for attenuating hematopoietic aging and, potentially, alleviating aging-associated immune remodeling and myeloid malignancies. Trends: HSC aging is associated with global epigenetic changes and shifts in cytoskeletal protein polarity. Mutations in both epigenetic modulators and spliceosome proteins have been shown to increase with age, and have been observed in healthy older individuals. Specific approaches and agents aiming to reverse global epigenetic profiles of aged HSCs are demonstrating promising rejuvenating capabilities. Senescent cell depletion approaches and agents have been shown to reverse or inhibit hematopoietic aging and certain aging-associated cancers in animal models.